Investigation on structural colours in wing scales of butterfly Papilio peranthus Fabricius. (1st January 2013) - Li, J.; Han, Q.; Chen, Y.; Zhu, Z.; Huang, W.
Abstract : The microstructure and geometrical dimensions of the scales on a butterfly Papilio peranthus Fabricius wing are obtained using scanning electron microscopy and transmission electron microscopy. Two kinds of scales are found in a butterfly wing and the structural colour mainly comes from the cover scale. Different structural models of cover scale that are related to ridge and concavity are constructed and their corresponding optical properties are investigated using the finite‐difference time‐domain method. It is concluded that the structural colour on the cover scale mainly comes from the sculpted multilayer structure and the ridge on the scale has few effects on the structural colour. When the curvature of the sculpted multilayer structure decreases, the dominant wavelength of colour will shift to a longer wavelength and move slower and slower. The two‐dimensional planar multilayer model can be used to calculate the structural colour when the curvature exceeds a certain value.